Green Accounting Affects Stock Prices And Financial Performance Of Sri Kehati Index - Corinna Fitriana; Indar Khaerunnisa (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
This study investigates the effect of green accounting on stock prices and financial performance in companies listed on the SRI-KEHATI Index from 2019 to 2023. Using a quantitative approach, the research analyzes secondary data from annual and sustainability reports of 14 selected companies, totaling 70 observations. Green accounting is measured by the ratio of environmental costs to net profit after tax, while stock price is represented by stock returns and financial performance by return on assets (ROA). The analysis includes classical assumption testing and simple linear regression. The results show that green accounting has a negative but insignificant effect on stock returns and a positive but also insignificant effect on ROA. This indicates that, during the observed period, green accounting practices did not significantly influence stock performance or financial outcomes in SRI-KEHATI listed firms. These findings imply that the market and company stakeholders may not yet fully integrate environmental accounting practices into their evaluation of company value and performance. Keywords : Green Accounting; Stock Return; Financial Performance; ROA; SRI-KEHATI.